2012
DOI: 10.1111/j.1553-2712.2012.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients Who Leave Without Being Seen in Emergency Departments: An Analysis of Predictive Factors and Outcomes

Abstract: Objectives: The objective was to identify predictive factors and outcomes associated with patients who leave emergency departments (EDs) without being seen in Victoria, Australia.Methods: This was a retrospective observational study of Victorian ED patient visits between July 1, 2000, and June 30, 2005, using linked hospital, ED, and death registration data. Index ED visits were identified for patients who left without being seen (LWBS) and for those who completed ED treatment and were discharged home. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 13 publications
7
43
0
2
Order By: Relevance
“…Extrapolating over an entire year, a sustained 1% decrease in the LWBT rate at the study institution would result in more than 500 additional adult patients being treated. As over 10% of patients who leave without being treated return to an ED for care within 72 hours, and approximately 4% are ultimately admitted to a hospital, 22,23,25 a sustained decrease in the LWBT rate would result in more timely provision of definitive care for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapolating over an entire year, a sustained 1% decrease in the LWBT rate at the study institution would result in more than 500 additional adult patients being treated. As over 10% of patients who leave without being treated return to an ED for care within 72 hours, and approximately 4% are ultimately admitted to a hospital, 22,23,25 a sustained decrease in the LWBT rate would result in more timely provision of definitive care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate predictor variables were selected based on literature review. 17,18,22,23 Those considered in the LWBT model included ED adult volume, ED low-acuity area volume, number of coded adult trauma activation patients, total ED wait time, total ED boarding hours, and ED nurse staffing hours. Candidate variables for the ED boarding model included number of ED admissions, number of ED admissions to the ICU, number of elective surgical admissions, hospital occupancy rate, ICU occupancy rate, and number of operational ICU beds.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7]27,30,43 Parmi les patients avec un code de triage de V, 27,5% (HF) et 34,2% (HD) ont fait un DAPCM. Par contre, la majoritĂ© (60%) des cas de DAPCM dans notre Ă©tude sont des patients ayant un code de triage de IV.…”
Section: Discussionunclassified
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Certains DAPCM peuvent avoir des codes de triage urgents. 14,20 Les facteurs les plus souvent associĂ©s au DAPCM sont : l'achalandage de l'urgence, 5,6,[21][22][23][24] le temps d'attente jugĂ© trop long, 4,5,9,10,17,20,[25][26][27][28][29] l'attribution d'un code de triage moins urgent, 5,6,17,20,27,[30][31][32][33] les caractĂ©ristiques intrinsĂšques du mĂ©decin de garde, 21,23 un jeune Ăąge, [5][6]…”
Section: Introductionunclassified
“…1,[12][13][14][15][16][17][18][19] It is a multifactorial problem that is, at its core, related to an imbalance between ED crowding and available resources. 20,21 LWBS rates are globally considered to be direct quality of care indicators, 3,25,[28][29][30] especially in paediatric services, 31,32 representing concerns for health care providers and policymakers. 3 Although some studies have indicated that LWBS are more likely to have non-urgent illnesses, 2,9,12,13,15,18 Revista CientĂ­fica da Ordem dos MĂ©dicos www.actamedicaportuguesa.com Sousa R, et al Children who leave the emergency department without being seen, Acta Med Port 2018 Feb;31 (2): [109][110][111][112][113][114] others have highlighted the potential risk of adverse outcomes, including the deterioration of patients' condition secondary to the delayed diagnosis or treatment.…”
Section: Introductionmentioning
confidence: 99%